Representasi Komunikasi Forensik pada Film Ice Cold - Rena Lela Putri; Septiawan Santana Kurnia (Bandung Conference Series: Public Relations, 2024)
Abstract. The murder case of Mirna Salihin, which sparked controversy and inspired the making of the documentary film "Ice Cold." This film attempts to depict the chronology of the murder and the lengthy trial, with the aim of providing a broader perspective to the audience. This research will analyze how forensic communication is represented in the film, focusing on the messages related to forensic communication conveyed and interpreted in the film. This study aims to analyze the representation of forensic communication in the film "Ice Cold" using Roland Barthes' semiotic approach.The research methodology utilized a constructivist paradigm with a qualitative approach and data collection techniques involving observation, interviews, and literature review. The research subject is the film "Ice Cold," while the research objects encompass coffee symbolism, forensic sign analysis, visual representation, dialogue, and social context within the film. Primary data was obtained through direct observation of the film, while secondary data originated from relevant literature.Data analysis stages involved data reduction, data presentation, and data verification. Data validity was examined through technical triangulation and observer triangulation. The research findings are expected to provide a profound understanding of how the film "Ice Cold" represents forensic communication and its implications on the public's perception and evaluation of the murder case. Based on the discussion in this study, the researcher concludes several results as follows: (1) The denotative meaning shows the forensic communication process in detail through gestures, expressions, and the presentation of objective scientific evidence, depicting the accuracy of the forensic process in the film. (2) The connotative meaning portrays the complexity, pressure, and uncertainty involved in the forensic process and their impact on the perception and emotional reactions of the characters. (3) The film presents various societal myths about legal and forensic processes, such as the absolute certainty of scientific evidence and the transparency of investigations. (4) The forensic process is not only about finding factual truth but also about maintaining integrity, thoroughness, and honesty in the disclosure of evidence. (5) The representation in the film influences public understanding of the complexity and challenges of the forensic process, encouraging a deeper and more critical understanding of criminal investigation procedures. Abstrak. Kasus pembunuhan Mirna Salihin yang menimbulkan kontroversi dan menginspirasi pembuatan film dokumenter "Ice Cold". Film ini mencoba menggambarkan kronologi peristiwa pembunuhan tersebut serta pengadilan yang berlangsung lama, dengan tujuan memberikan perspektif yang lebih luas kepada penonton. Penelitian ini akan menganalisis bagaimana komunikasi forensik direpresentasikan dalam film tersebut, dengan fokus pada pesan-pesan terkait komunikasi forensik yang disampaikan dan diinterpretasikan dalam film. Penelitian ini bertujuan untuk menganalisis representasi komunikasi forensik dalam film "Ice Cold" dengan menggunakan pendekatan semiotika Roland Barthes. Metode penelitian yang digunakan adalah paradigma konstruktivis dengan pendekatan kualitatif dan teknik pengumpulan data berupa observasi, wawancara, dan studi pustaka. Subjek penelitian adalah film "Ice Cold," sementara objek penelitian mencakup simbolisme kopi, analisis tanda forensik, representasi visual, dialog, dan konteks sosial dalam film. Data primer diperoleh melalui observasi langsung terhadap film, sedangkan data sekunder berasal dari literatur terkait.Tahap analisis data melibatkan reduksi data, penyajian data, dan verifikasi data. Keabsahan data diuji melalui triangulasi teknis dan triangulasi pengamat. Hasil penelitian menunjukkan bahwa (1) Makna denotasi menunjukkan proses komunikasi forensik secara detail melalui gestur, ekspresi, dan presentasi bukti ilmiah yang objektif, menggambarkan akurasi proses forensik dalam film. (2) Makna konotasi menggambarkan kompleksitas, tekanan, dan ketidakpastian dalam proses forensik serta dampaknya terhadap persepsi dan reaksi emosional karakter. (3) Film ini mengangkat berbagai mitos masyarakat tentang proses hukum dan forensik, seperti kepastian absolut dari bukti ilmiah dan transparansi investigasi. (4) Proses forensik tidak hanya tentang menemukan kebenaran faktual, tetapi juga mempertahankan integritas, ketelitian, dan kejujuran dalam pengungkapan bukti. (5) Representasi dalam film mempengaruhi pemahaman masyarakat tentang kompleksitas dan tantangan proses forensik, mendorong pemahaman yang lebih mendalam dan kritis terhadap proses investigasi kriminal.